Technology Of Physical Development Of Students With The Help Of Physical Education Means - Ochilova Farida Bakhriddinovna; Mizomov Shakhriddin Sag’dullayevich (Zien Journals, 2025)
This article discusses the processes of physical education of students based on the technology of physical development using physical education equipment and the techniques and means of physical training and fitness used in these processes
Keywords: physical education; physical education equipment; fitness